Culture of care: the debate between history and pre-profissional nursing in watercolors of Jean-Baptiste Debret (1816-1831) - Paulo Fernando Souza Campos (Universidad de Alicante, 2015)
To identify practices to care for and cure performed by black men and women, the study evokes the historical context marked by the transfer of the Portuguese Crown (1808-1820) to Brazil, social space meant as conducive to the development of diseases. Legacy pictorial records of the work of Jean-Baptiste Debret, preserved in the Museum Castro Maya, Rio de Janeiro, were used as the source and the results are social places of care and its performers as well as the links between History and History of Pre-Professional Brazilian Nursing in their oblique relations with the culture of care.